Nickel-clad copper composite strip with high bonding strength and preparation method thereof
By adding a transition metal layer to the nickel-copper-clad composite strip and heating and pressurization treatment, the problem of low bonding strength of the nickel-copper composite strip is solved, and the conductivity and service life are significantly improved.
Patent Information
- Application Number
- CN202211247732.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-12
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2042-10-12
AI Technical Summary
During the rolling process, the existing nickel-copper composite strips have low binding strength and reduced electrical conductivity due to the solid solution α between the diffusion layer gap between Cu and Ni.
The preparation method of nickel-covered copper composite strip is adopted. By adding a transition metal layer, such as titanium, manganese, chromium, silver, and lanthanum, between the copper core and the nickel tube, the diffusion and bonding between the transition metal and copper and nickel are promoted, and the fine cracks between the metal are filled and the bonding strength is enhanced.
The bonding strength and conductivity of nickel-clad copper-clad composite strip are significantly improved, preventing copper from being exposed to air, extending service life, and simplifying the process.
Smart Images

Figure CN115440415B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite metal strips, and in particular to a nickel-clad copper composite strip with high bonding strength and a preparation method thereof. Background Art
[0002] Nickel-copper composite strips are widely used in the fields of batteries, electrical components, etc. For example, the tabs of soft-pack batteries and cylindrical batteries. Tabs are conductors pulled out from the battery electrodes. Traditional tabs use nickel strips, which have poor conductivity; the improved tabs use copper-plated nickel strips, in which the nickel layer is responsible for welding and meshing with the battery electrodes, and the copper layer provides good conductivity. Although this component guarantees conductivity and welding performance, since both sides of the copper are not completely covered with nickel layers, one side of the copper is exposed to the outside and in direct contact with the electrolyte, causing the electrolyte to corrode along the copper layer. At the same time, during the rolling and compounding process of nickel and copper metal layers, a diffusion layer interstitial solid solution α based on Ni is formed between Cu and Ni. In the diffusion reaction layer α, Cu atoms diffuse and migrate from the end close to the Cu / α phase interface to the end close to the α / Ni phase interface by a vacancy diffusion mechanism, while Ni atoms are extremely difficult to enter the diffusion reaction layer α. In the diffusion reaction process of nickel and copper, the Cu / α interface is equivalent to the atomic input end, the α / Ni interface is equivalent to the atomic output end, and the diffusion reaction layer α plays the role of transporting atoms. This phenomenon results in a large number of pores on the metallic copper side, while very few nickel atoms diffuse to the copper side, resulting in low bonding strength between the copper and nickel layers and reduced conductivity.
[0003] For example, Chinese patent CN201710744998.X discloses a method and a bonding part for the interface bonding of a binary pseudoalloy and an alloy containing a transition metal, wherein tungsten doped with copper and filter metals including nickel are sintered at high pressure and 1000 degrees to enhance the bonding strength, and the enhancement effect of the bonding strength varies depending on the metal material used and the setting of the temperature parameters. Summary of the invention
[0004] In view of the problem of lack of preparation process for enhancing the bonding strength of nickel-clad copper composite strips in the prior art, the present invention provides a nickel-clad copper composite strip with high bonding strength, which has the advantage of high bonding strength between different metal layers; the present invention also provides a method for preparing the nickel-clad copper composite strip with high bonding strength, and the prepared nickel-clad copper composite strip has the advantage of high bonding strength between different metal layers.
[0005] The present invention is achieved by the following technical solutions:
[0006] A nickel-clad copper composite strip with high bonding strength, the composite strip comprises a rod-shaped copper core, a transition metal tube and an outermost nickel tube from the inside to the outside; both ends of the copper core are fully enclosed by the nickel tube; metal atoms between the copper core and the transition metal tube, and between the transition metal tube and the nickel tube diffuse mutually; the transition metal tube is one of titanium, manganese, chromium, silver and lanthanum.
[0007] Since copper and nickel form a solid solution that hinders diffusion when heated, it is difficult for atoms to diffuse into each other. By adding a transition metal layer that is easy to diffuse with copper and nickel, the diffusion difficulty between the transition metal and copper or nickel is greatly reduced. Under the condition of heating and pressurization, the transition metal and copper and nickel combine and diffuse with each other, filling the tiny cracks between different metals, which greatly increases the bonding strength between different metals. Different transition metals are selected and different heating annealing temperatures are selected to achieve the purpose of reducing cracks between the transition metal layer and the copper-nickel interface and enhancing the bonding strength.
[0008] Preferably, the diameter of the copper core is equal to the inner diameter of the transition metal tube, and the outer diameter of the transition metal tube is equal to the inner diameter of the nickel tube; and the cross-sectional area of the transition metal tube is less than or equal to 20% of the cross-sectional area of the copper rod, and less than or equal to 10% of the cross-sectional area of the nickel tube. A suitable cross-sectional area ratio of the copper-nickel tube and the transition metal tube is conducive to maintaining the electrical conductivity within an appropriate range; the thickness of the composite strip is 100 to 250 μm, and the thickness of the composite strip affects the electrical conductivity.
[0009] A method for preparing a nickel-clad copper composite strip with high bonding strength comprises the following steps:
[0010] 1) inserting the copper core into the transition metal tube, and then inserting the transition metal tube-wrapped copper core into the nickel tube to form a composite metal rod;
[0011] 2) cold forging the composite metal rod prepared in step 1) into a composite metal plate, and annealing;
[0012] 3) heating the composite metal plate prepared in step 2) and pre-cold rolling it once;
[0013] 4) cold rolling the composite metal plate pre-cold rolled in step 3) through a series of rollers for one time and then annealing, and repeating this process for multiple times to obtain a nickel-clad copper composite strip;
[0014] 5) The nickel-clad copper composite strip prepared in step 4) is placed in water containing a surfactant for ultrasonic cleaning.
[0015] After preparation, the two ends of the nickel tube-wrapped copper tube will be welded to completely seal the two ends of the copper so that the two ends cannot be corroded. The main part of the copper wrapped by nickel plays a major role in conductivity. Wrapping copper with nickel greatly reduces the possibility of copper corrosion, maintaining the electrical conductivity and service life of the composite strip. After the two ends of the strip are welded, the air and copper are completely isolated.
[0016] Preferably, in step 1), the diameter of the copper core is equal to the inner diameter of the transition metal tube, and the outer diameter of the transition metal tube is equal to the inner diameter of the nickel tube; and the cross-sectional area of the transition metal tube is less than or equal to 20% of the cross-sectional area of the copper rod, and less than or equal to 10% of the cross-sectional area of the nickel tube.
[0017] Preferably, the thickness of the composite metal plate obtained in step 2) is greater than or equal to 3 cm and less than or equal to 5 cm.
[0018] Preferably, the cold rolling temperature in step 3) is lower than the lowest recrystallization temperature of any metal in the composite metal plate, and is greater than or equal to the lowest recrystallization temperature -50K.
[0019] Preferably, the cold rolling temperature in step 4) is less than the lowest recrystallization temperature of any metal in the composite metal plate, and greater than or equal to the lowest recrystallization temperature -50K (Kelvin temperature);
[0020] Preferably, the tandem rollers described in step 4) include several upper and lower rollers arranged in parallel with each other, and the spacing between each pair of upper and lower rollers decreases successively by less than or equal to 10% of the thickness of the composite metal plate before the rolling. After the tandem rolling is completed once, the thickness of the strip becomes 1 / 2 of that before rolling, which can prevent the generation of cracks during the rolling process.
[0021] Preferably, in steps 2) and 4), the annealing temperature is greater than or equal to 473K (Kelvin temperature), the heating rate is 8-12K / min, and the holding time is 4h.
[0022] Preferably, in steps 2) and 4), the greater the annealing temperature and the electronegativity difference between the transition metal element and copper and nickel, the greater the difference in atomic radius, the greater the difference in arrangement, the greater the diffusion activation energy, the greater the crystal defect density, the greater the diffusion difficulty, and the higher the required temperature, so as to ensure that different metal atoms have sufficient power to penetrate each other.
[0023] Preferably, when the thickness of the composite metal plate is less than 1 mm, the series rollers may not all be in the same plane, which can save space. The thin composite metal plate less than 1 mm can remain flat after passing through all the series rollers and is less likely to crack.
[0024] Beneficial effects of the present invention:
[0025] (1) Adding a transition metal layer between copper and nickel reduces the electronegativity difference between the metal elements at the interface, which also reduces the difficulty of diffusion between the interface metals. Small cracks disappear as they are filled with mutual diffusion, and the bonding strength is enhanced.
[0026] (2) During the rolling process, different heating and annealing temperature parameters are selected for different transition metals, and the bonding strength is significantly enhanced.
[0027] (3) During the rolling process, tandem rollers are used and the distance between each pair of upper and lower rollers is reduced by an amount less than or equal to 10% of the thickness of the composite metal plate before the rolling process to prevent cracks from being generated during the rolling process.
[0028] (4) The bonding strength between metal layers is enhanced, which increases the electrical conductivity of the composite strip.
[0029] (5) Nickel is wrapped around copper to prevent it from corroding and rusting when exposed to air.
[0030] (6) A wide range of transition metal options helps manufacturers cope with rising raw material prices with multiple options.
[0031] (7) The process is simplified and the materials used are simple, which is conducive to industrial promotion. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 Schematic diagram of the cross section of the strip after rolling.
[0033] Figure 2 Schematic diagram of the strip passing through the rolling rollers in the same plane.
[0034] Figure 3 Schematic diagram of the strip passing through rolling rollers in different planes. DETAILED DESCRIPTION
[0035] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only some embodiments of the present invention, not all. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] Example 1
[0037] A method for preparing a nickel-clad copper composite strip with high bonding strength is completed by the following steps: using titanium as a transition layer, the diameter of the copper rod is 20 mm, the inner diameter of the titanium tube is 20 mm, the outer diameter of the titanium tube is 21 mm, the inner diameter of the nickel tube is 21 mm, and the outer diameter of the nickel tube is 30 mm. The copper, titanium, and nickel are inserted into each other from the inside to the outside and then cold forged. A mold with a limited width of 200 mm is selected, and the metal plate thickness is about 3.5 mm after cold forging. Annealing, the annealing temperature is 1072 K, and the pre-cold rolling is heated to 673 K (Kelvin temperature). The roller spacing is set to 3.2 mm, the roller linear speed is 5 mm / s, and the width change is less than 20%; 5 pairs of rollers are connected in series for continuous rolling, the roller linear speed is 5mm / s, the annealing temperature is 1073K, annealing and heat preservation are 4h and then placed in air for cooling; rolling and annealing are repeated four times, the strip thickness is rolled to 1.6mm for the first time, and the spacing between each pair of rollers is reduced by 0.32mm; the strip thickness is rolled to 0.8mm for the second time, and the spacing between each pair of rollers is reduced by 0.16mm; the strip thickness is rolled to 0.4mm for the third time, and the spacing between each pair of rollers is reduced by 0.08mm; the strip thickness is rolled to 0.2mm for the fourth time, and the spacing between each pair of rollers is reduced by 0.04mm.
[0038] Example 2
[0039] A method for preparing a nickel-clad copper composite strip with high bonding strength is completed by the following steps: using manganese as a transition layer, the diameter of the copper rod is 20 mm, the inner diameter of the manganese tube is 20 mm, the outer diameter of the manganese metal tube is 21 mm, the inner diameter of the nickel tube is 21 mm, and the outer diameter of the nickel tube is 30 mm, inserting copper, manganese and nickel into each other from the inside to the outside in sequence and then cold forging, selecting a mold with a limited width of 200 mm, cold forging to obtain a metal plate with a thickness of about 3.5 mm, annealing, the annealing temperature is 1073 K, pre-cold rolling, heating the temperature to 673 K, setting the roller spacing to 3.2 mm, the roller linear speed to 5 mm / s, and the width change is less than 2 0%; 5 pairs of rollers are connected in series for continuous rolling, the roller linear speed is 5mm / s, the annealing temperature is 1073K, the annealing is kept for 4h, and then cooled in air; the rolling and annealing are repeated four times, the strip thickness is rolled to 1.6mm for the first time, and the spacing between each pair of rollers is decreased by 0.32mm; the strip thickness is rolled to 0.8mm for the second time, and the spacing between each pair of rollers is decreased by 0.16mm; the strip thickness is rolled to 0.4mm for the third time, and the spacing between each pair of rollers is decreased by 0.08mm; the strip thickness is rolled to 0.2mm for the fourth time, and the spacing between each pair of rollers is decreased by 0.04mm.
[0040] Example 3
[0041] A method for preparing a nickel-clad copper composite strip with high bonding strength is completed by the following steps: using chromium as a transition layer, the diameter of the copper rod is 20 mm, the inner diameter of the chromium tube is 20 mm, the outer diameter of the chromium tube is 21 mm, the inner diameter of the nickel tube is 21 mm, and the outer diameter of the nickel tube is 30 mm; inserting copper, chromium and nickel into each other from the inside to the outside in sequence and then cold forging, selecting a mold with a limited width of 200 mm, and obtaining a metal plate with a thickness of about 3.5 mm, annealing, the annealing temperature is 1073 K, pre-cold rolling, heating the temperature to 673 K (Kelvin temperature), setting the roller spacing to 3.2 mm, the roller linear speed to 5 mm / s, and the width change is less than 20%;
[0042] Five pairs of rollers are connected in series for continuous rolling, with a roller linear speed of 5 mm / s, an annealing temperature of 1073 K, annealing and insulation for 4 hours, and cooling in air; rolling and annealing are repeated four times, the strip thickness is rolled to 1.6 mm for the first time, and the spacing between each pair of rollers decreases by 0.32 mm; the strip thickness is rolled to 0.8 mm for the second time, and the spacing between each pair of rollers decreases by 0.16 mm; the strip thickness is rolled to 0.4 mm for the third time, and the spacing between each pair of rollers decreases by 0.08 mm; the strip thickness is rolled to 0.2 mm for the fourth time, and the spacing between each pair of rollers decreases by 0.04 mm.
[0043] Example 4
[0044] A method for preparing a nickel-clad copper composite strip with high bonding strength is completed by the following steps: using silver as a transition layer, the diameter of the copper rod is 20 mm, the inner diameter of the silver tube is 20 mm, the outer diameter of the silver tube is 21 mm, the inner diameter of the nickel tube is 21 mm, and the outer diameter of the nickel tube is 30 mm; inserting copper, silver, and nickel into each other from the inside to the outside in sequence and then cold forging, selecting a mold with a limited width of 200 mm, and obtaining a metal plate with a thickness of about 3.5 mm, annealing, the annealing temperature is 673 K, pre-cold rolling, heating the temperature to 673 K, setting the roller spacing to 3.2 mm, the roller linear speed to 5 mm / s, and the width change is less than 20%; 5 pairs The rollers are connected in series for continuous rolling, with a roller linear speed of 5 mm / s, an annealing temperature of 673 K (Kelvin temperature), annealing and insulation for 4 hours, and cooling in air; the rolling annealing is repeated four times, the strip thickness is rolled to 1.6 mm for the first time, and the spacing between each pair of rollers is decreased by 0.32 mm; the strip thickness is rolled to 0.8 mm for the second time, and the spacing between each pair of rollers is decreased by 0.16 mm; the strip thickness is rolled to 0.4 mm for the third time, and the spacing between each pair of rollers is decreased by 0.08 mm; the strip thickness is rolled to 0.2 mm for the fourth time, and the spacing between each pair of rollers is decreased by 0.04 mm.
[0045] Example 5
[0046] A method for preparing a nickel-clad copper composite strip with high bonding strength is completed by the following steps: using lanthanum as a transition layer, the diameter of the copper rod is 20 mm, the inner diameter of the lanthanum tube is 20 mm, the outer diameter of the lanthanum tube is 21 mm, the inner diameter of the nickel tube is 21 mm, and the outer diameter of the nickel tube is 30 mm; inserting copper, lanthanum and nickel into each other from the inside to the outside in sequence and then cold forging, using a mold with a limited width of 200 mm, to obtain a metal plate with a thickness of about 3.5 mm, annealing, the annealing temperature is 673 K, pre-cold rolling, heating the temperature to 673 K, setting the roller spacing to 3.2 mm, the roller linear speed to 5 mm / s, and the width change is less than 20%;
[0047] Five pairs of rollers are connected in series for continuous rolling, with a roller linear speed of 5 mm / s, an annealing temperature of 673 K, annealing and insulation for 4 hours, and cooling in air; the rolling annealing is repeated four times, the strip thickness is rolled to 1.6 mm for the first time, and the spacing between each pair of rollers decreases by 0.32 mm; the strip thickness is rolled to 0.8 mm for the second time, and the spacing between each pair of rollers decreases by 0.16 mm; the strip thickness is rolled to 0.4 mm for the third time, and the spacing between each pair of rollers decreases by 0.08 mm; the strip thickness is rolled to 0.2 mm for the fourth time, and the spacing between each pair of rollers decreases by 0.04 mm.
[0048] Comparative Example 1:
[0049] A method for preparing a nickel-clad copper composite strip is completed by the following steps: without using a transition metal layer, the diameter of the copper rod is 21 mm, the inner diameter of the nickel tube is 21 mm, the outer diameter of the nickel tube is 30 mm, the copper is inserted into the nickel tube for cold forging, a mold with a limited width of 200 mm is selected, and the thickness of the metal plate is about 3.5 mm, annealing, the annealing temperature is 1073 K, pre-cold rolling, the temperature is heated to 673 K (Kelvin temperature), the roller spacing is set to 3.2 mm, the roller linear speed is 5 mm / s, and the width change is less than 20%; 5 pairs of rollers are connected in series for continuous rolling, The roller linear speed is 5mm / s, the annealing temperature is 1073K, the annealing is kept for 4h, and then cooled in air; the rolling annealing is repeated four times, the strip thickness is rolled to 1.6mm in the first time, and the spacing between each pair of rollers is decreased by 0.32mm; the strip thickness is rolled to 0.8mm in the second time, and the spacing between each pair of rollers is decreased by 0.16mm; the strip thickness is rolled to 0.4mm in the third time, and the spacing between each pair of rollers is decreased by 0.08mm; the strip thickness is rolled to 0.2mm in the fourth time, and the spacing between each pair of rollers is decreased by 0.04mm.
[0050] Comparative Example 2
[0051] A method for preparing a nickel-clad copper composite strip is completed by the following steps:
[0052] The difference from Example 4 is that the annealing temperature is 873K.
[0053] Silver is used as a transition layer, the diameter of the copper rod is 20 mm, the inner diameter of the silver tube is 20 mm, the outer diameter of the silver tube is 21 mm, the inner diameter of the nickel tube is 21 mm, and the outer diameter of the nickel tube is 30 mm; copper, silver, and nickel are inserted into each other from the inside to the outside and then cold forged, and a mold with a limited width of 200 mm is selected to obtain a metal plate with a thickness of about 3.5 mm. Annealing, the annealing temperature is 873 K, and the pre-cold rolling is heated to 673 K. The roller spacing is set to 3.2 mm, the roller linear speed is 5 mm / s, and the width change is less than 20%; 5 pairs of rollers are connected in series for continuous rolling, and the roller linear speed is 5mm / s, annealing temperature is 873K (Kelvin temperature), annealing and heat preservation are 4h, and cooling is carried out in air; rolling annealing is repeated four times, the strip thickness is rolled to 1.6mm for the first time, and the spacing between each pair of rollers is decreased by 0.32mm; the strip thickness is rolled to 0.8mm for the second time, and the spacing between each pair of rollers is decreased by 0.16mm; the strip thickness is rolled to 0.4mm for the third time, and the spacing between each pair of rollers is decreased by 0.08mm; the strip thickness is rolled to 0.2mm for the fourth time, and the spacing between each pair of rollers is decreased by 0.04mm.
[0054] Comparative Example 3
[0055] A method for preparing a nickel-clad copper composite strip is completed by the following steps:
[0056] Zinc is used as a transition layer, the diameter of the copper rod is 20mm, the inner diameter of the zinc tube is 20mm, the outer diameter of the zinc tube is 21mm, the inner diameter of the nickel tube is 21mm, and the outer diameter of the nickel tube is 30mm; copper, zinc, and nickel are inserted into each other from the inside to the outside and then cold forged, a mold with a limited width of 200mm is selected, and the thickness of the metal plate obtained by cold forging is about 3.5mm, annealing, the annealing temperature is 523K, and the pre-cold rolling stabilizes the temperature at 423K (Kelvin temperature), sets the roller spacing to 3.2mm, the roller linear speed is 5mm / s, and the width change is less than 20%; 5 pairs of rollers are connected in series for continuous rolling Rolling, the roller line speed is 5mm / s, the annealing temperature is 423K, the annealing is kept for 4h, and the cooling is carried out in the air; the rolling and annealing are repeated four times, the strip thickness is rolled to 1.6mm for the first time, and the spacing between each pair of rollers is decreased by 0.32mm; the strip thickness is rolled to 0.8mm for the second time, and the spacing between each pair of rollers is decreased by 0.16mm; the strip thickness is rolled to 0.4mm for the third time, and the spacing between each pair of rollers is decreased by 0.08mm; the strip thickness is rolled to 0.2mm for the fourth time, and the spacing between each pair of rollers is decreased by 0.04mm.
[0057] Detection method:
[0058] The conductivity was measured by a DC resistance tester to obtain the resistance R, the sample length L = 100 cm, the cross-sectional area S = 0.02 × 0.4 = 0.008 cm2, and the resistivity ρ = RS / L and the conductivity G = 1 / ρ were calculated; the tensile strength and peel strength were tested by a universal mechanical testing machine, the sample length was 100 mm, the width was 20 mm, and the height was 0.2 mm, the experimental speed was set to 100 mm / min, and then the sample was cut into thin slices longitudinally and the cross section was analyzed by backscattering using SEM, and the data obtained were as follows Table 1:
[0059]
[0060]
[0061] As shown in Table 1, in Example 1, the overall performance of electrical conductivity, tensile strength and peel strength obtained by using titanium as the transition metal layer is optimal, nickel can diffuse to the titanium-copper interface, and the three metal atoms penetrate each other evenly, preventing the generation of crack holes; in Example 2, manganese is used as the transition metal. Due to the presence of α-Mn filling at the interface, after the crack holes at the interface are filled, there are fewer interface defects between manganese-nickel and manganese-copper; in Example 3, chromium is used as the transition metal layer, and Cr-rich bcc phase and Ni-rich fcc phase will precipitate at the nickel-chromium interface; Cr-rich bcc phase and Cu-rich fcc phase will be generated at the copper-chromium interface, and the two balances are achieved locally, so that the interface Dense and free of pores and cracks; Example 4 uses silver as the transition metal layer, which improves the electrical conductivity, and when annealed at 673K, solid-phase sintering occurs over time, and the tiny holes and cracks inside the interface gradually heal, forming a relatively dense structure, reducing cracks and voids. The 673K diffusion annealing promotes the homogenization of crack voids, so that the tensile strength and peel strength remain stable; Example 5 uses lanthanum as the transition metal layer. Due to the solid-phase sintering, the tiny holes and cracks inside the interface gradually heal, forming a relatively dense structure and reducing cracks. However, due to the large difference in the atomic radius of metal lanthanum and copper and nickel, the vacancy mechanism is prevented. The diffusion of the control system is not obvious at the interface, so the diffusion phenomenon at the interface is not obvious, and the tensile strength and peel strength are slightly lower than those of other embodiments; Comparative Example 1 has no transition metal layer, and there are a large number of pores and cracks between the copper and nickel interfaces, so the tensile strength and peel strength are lower than those of the embodiments; Comparative Example 2 uses silver as the transition metal layer and increases the annealing temperature to 873K (Kelvin temperature), and the number of pores and cracks at the interface increases significantly, and the uniformity deteriorates. This may be due to the high temperature, long annealing time, the shrinkage of the volume of particles between adjacent layers at the interface, and the overflow of dissolved gases, etc., and the tensile strength and peel strength are also significantly lower than those of Example 4; Comparative Example 3 uses zinc as the transition metal layer, and the zinc and nickel elements are electrically The negative phase is far different, not easy to diffuse, and there are many cracks and gaps between the interfaces, while the diffusion between the zinc and copper interfaces is relatively uniform, without obvious cracks, but in terms of conductivity, tensile strength and peel strength, Comparative Example 3 has the lowest performance among all embodiments and comparative examples. This is because the transition metal layer mainly affects the tensile strength, and the tensile strength of zinc itself is relatively low. The zinc rod will come into contact with the air at room temperature to generate non-conductive basic zinc carbonate. At the same time, when the temperature is heated to 523K during the annealing process, the nature of zinc is extremely active, and it will generate compounds with the carbon dioxide and oxygen remaining in the gaps. The generated compound particles are not only non-conductive, but also affect the diffusion process, thereby affecting the bonding strength of the interface.
[0062] like Figure 1 As shown, nickel is wrapped around the copper core to prevent the copper core from being oxidized by the outside world. Figure 2 As shown in the figure, the strip first passes through the rolling rollers on the same plane, and when the thickness is compressed to less than 1mm, it passes through the rolling rollers on different planes. Figure 3As shown, the flatness of the strip after rolling can still be maintained, and cracks can be prevented from occurring at the corners of the strip during the rolling process.
[0063] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0064] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A nickel-clad copper composite strip with high bonding strength, characterized in that: The composite strip comprises a rod-shaped copper core, a transition metal tube and an outermost nickel tube from the inside to the outside; metal atoms diffuse mutually between the copper core and the transition metal tube, and between the transition metal tube and the nickel tube; the transition metal tube is one of titanium, manganese, chromium, silver and lanthanum; and the preparation method comprises the following steps: 1) inserting the copper core into the transition metal tube, and then inserting the transition metal tube-wrapped copper core into the nickel tube to form a composite metal rod; 2) cold forging the composite metal rod prepared in step 1) into a composite metal plate, and annealing; 3) heating the composite metal plate prepared in step 2) and pre-cold rolling it once; 4) cold rolling the composite metal plate pre-cold rolled in step 3) through a series of rollers once and then annealing, and repeating the process for multiple times to obtain a nickel-clad copper composite strip; 5) placing the nickel-clad copper composite strip prepared in step 4) in water containing a surfactant for ultrasonic cleaning; The cold rolling temperature in step 3) is lower than the lowest recrystallization temperature of any metal in the composite metal plate and is greater than or equal to the lowest recrystallization temperature -50K; The cold rolling temperature in step 4) is lower than the lowest recrystallization temperature of any metal in the composite metal plate and is greater than or equal to the lowest recrystallization temperature -50K; The annealing temperature in steps 2) and 4) is greater than or equal to 473K, the heating rate is 8-12K / min, and the holding time is 4h.
2. A nickel-clad copper composite strip with high bonding strength according to claim 1, characterized in that: The copper core diameter is equal to the inner diameter of the transition metal tube, and the outer diameter of the transition metal tube is equal to the inner diameter of the nickel tube; and the cross-sectional area of the transition metal tube is less than or equal to 20% of the cross-sectional area of the copper rod, and less than or equal to 10% of the cross-sectional area of the nickel tube; the thickness of the composite strip is 100-250 μm.
3. The nickel-clad copper composite strip with high bonding strength according to claim 1, characterized in that: In step 1), the diameter of the copper core is equal to the inner diameter of the transition metal tube, and the outer diameter of the transition metal tube is equal to the inner diameter of the nickel tube; and the cross-sectional area of the transition metal tube is less than or equal to 20% of the cross-sectional area of the copper rod, and less than or equal to 10% of the cross-sectional area of the nickel tube.
4. The nickel-clad copper composite strip with high bonding strength according to claim 1, characterized in that: The thickness of the composite metal plate obtained in step 2) is greater than or equal to 3 cm and less than or equal to 5 cm.
5. The nickel-clad copper composite strip with high bonding strength according to claim 1, characterized in that: The tandem rollers in step 4) include several pairs of upper and lower rollers arranged in parallel with each other, and the spacing between each pair of upper and lower rollers decreases successively, and the amount of reduction in the spacing is less than or equal to 10% of the thickness of the composite metal plate before the rolling. After the tandem rolling is completed once, the thickness of the strip becomes 1 / 2 of that before rolling.
Citation Information
Patent Citations
Interface bonding method and binder between binary pseudo-alloy and alloy containing transition metal
CN107584127A
Copper-nickel alloy tube preparation method
CN102899595A
Manufacturing process of oxide series superconductive wire
CN1034632A